Minimally invasive gastrectomy for gastric adenocarcinoma in the United States: Utilization and short‐term oncologic outcomes. Issue 6 (23rd September 2015) - Ecker, Brett L.; Datta, Jashodeep; McMillan, Matthew T.; Poe, Sarah‐Lucy C.; Drebin, Jeffrey A.; Fraker, Douglas L.; Dempsey, Daniel T.; Karakousis, Giorgos C.; Roses, Robert E.
<x xml:space="preserve">Abstract</x> Background and Objectives When performed at select centers, minimally invasive gastrectomy (MIG) for gastric adenocarcinoma is associated with reduced perioperative morbidity, and similar oncologic outcomes as compared to open gastrectomy (OG). Utilization of, and outcomes associated with, MIG in the United States have not been characterized. Methods The National Cancer Database (2010–2011) was queried for AJCC pStage IB‐IIIC patients who underwent curative‐intent OG (n = 2, 303) or MIG (n = 331). Multivariable models identified factors associated with MIG utilization, R0 resection rates, and adequate lymph node staging (LNS). Results MIG was more frequently utilized for T1/T2 (P < 0.001), N0 (P = 0.022), and stage IB (P = 0.001) tumors. MIG was associated with shorter hospital stay (P < 0.001), equivalent lymph node examination (P = 0.337) and superior rates of R0 resection (P = 0.011) compared with OG. In patients undergoing MIG, R0 resection was associated with performance of near‐total/total gastrectomy (OR 3.90, 95%CI 1.10–13.9) and tumors < 5 cm (OR 2.78, 95%CI 1.07–7.26). Adequate LNS was associated with surgery at academic (OR 1.99, 95%CI 1.19–3.32) or high‐volume facilities (OR 2.97, 95%CI 1.59–5.54), tumor size ≥ 5 cm (OR 1.85, 95%CI 1.10–3.11), and node positivity (OR 1.75, 95%CI 1.04–2.93). Conclusions MIG is selectively utilized in cases with favorable tumor characteristics. In such cases, short‐term oncologic outcomes are equivalent to those achieved with OG. Worse oncologic outcomes in specific subgroups underscore opportunities for quality improvement. J. Surg. Oncol. 2015;112:616–621. © 2015 Wiley Periodicals, Inc.